Influence of the surface finishing on the wear behaviour of cemented carbides worked by Electrical Discharge Machining. (June 2023) - Sordetti, F.; Magnan, M.; Carabillò, A.; Querini, M.; Fedrizzi, L.; Lanzutti, A.
Abstract: Cermets are materials, usually made of hard ceramic particles embedded in metal matrix, widely used in different technological fields typically produced by powder metallurgy processes. The combination of the two materials results in a material with superior properties respect to either material alone. One of the most used technology to obtain the final shape of the cermets is the Electrical Discharge Machining process (EDM), which involve some microstructural alterations that influence the tribological behaviour. In this work, several cermet samples were processed using the EDM process. The samples were then subjected to different surface finishing processes such as sandblasting, grinding, lapping and their combinations to reduce the effect of the EDM altered surface layer. The near surface of the samples was analysed in terms of: microstructure (SEM + EDX), surface texture (stylus profilometer), chemical composition (RF-GDOES). A detailed tribological characterization was performed in ball-on-flat configuration at several different loads (20 N, 40 N, 80 N) in order to simulate similar conditions of cold rolling rolls. The worn samples were then characterized in order to measure the wear rate and identify the wear mechanisms. The obtained results showed that the EDM process leaves an altered layer that alters the surface of the samples and influences the wear performance of the sample. The removal of this layer completely change the tribological material response in terms of wear rate and coefficient of friction. Highlights: The EDM process involves microstructural alterations on the surface of the cermet. The analysed samples were sandblasted, ground, and lapped. Tribological tests at low loads are strongly influenced by the surface finishing. Tribological tests at high loads are not influenced by the surface finishing.